Financial Globalization : a Reappraisal. (IMF working paper ;, 2006)
The literature on the benefits and costs of financial globalization for developing countries has exploded in recent years, but along many disparate channels and with a variety of apparently conflicting results. For instance, there is still little robust evidence of the growth benefits of broad capital account liberalization, but a number of recent papers in the finance literature report that equity market liberalizations do significantly boost growth. Similarly, evidence based on microeconomic (firm- or industry-level) data shows some benefits of financial integration and the distortionary effects of capital controls, while the macroeconomic evidence remains inconclusive. We attempt to provide a unified conceptual framework for organizing this vast and growing literature. This framework allows us to provide a fresh synthetic perspective on the macroeconomic effects of financial globalization, in terms of both growth and volatility. Overall, our critical reading of the recent empirical literature is that it lends some qualified support to the view that developing countries can benefit from financial globalization, but with many nuances. On the other hand, there is little systematic evidence to support widely cited claims that financial globalization by itself leads to deeper and more costly developing country growth crises.